The first in-beam reaction measurement at CRYRING@ESR using the CARME array - Marsh, Jordan J.; Bruno, Carlo G.; Davinson, Thomas; Woods, Philip J.; Andelkovic, Zoran; Bräuning-Demian, Angela; Chen, Rui-Jui; Dellmann, Sophia Florence; Erbacher, Phillip; Fedotova, Svetlana; Forstner, Oliver; Freire Fernández, David; et al. (The European physical journal. A, Hadrons and nuclei, 2024)
In the last decade nuclear reaction measurements using heavy ion storage rings became an important tool for nuclear astrophysics studies. The new CRYRING Array for Reaction MEasurements (CARME), recently commissioned at the low energy CRYRINGESR storage ring (GSI/FAIR), is designed to take this novel approach one step further and perform direct nuclear reaction measurements at stellar energies, as well as indirect studies of nuclear properties of interest for nuclear astrophysics. CRYRING is unique worldwide in being able to store high quality, isotopically pure, radioactive beams produced in-flight at the low energies required for nuclear astrophysics. This paper describes the first in-beam reaction measurement with CARME at CRYRING, the first beam on (conventional) target measurement for FAIR Phase-0, and the data analysis approach required by this unprecedented, unique experimental approach.
Gesehen am 28.10.2024